FACTORS THAT INFLUENCE MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) OWNERS TO PAY ZAKAT - -, Elfiswandi; Very, John (Jurnal Ipteks Terapan, 2024)
Zakat is part from system economy Islam. Order zakat aim For balance economy, Which capable move all over potential and optimization of the economic power of the people. The increasing number of micro entrepreneurs in urban areas , especially in the city of Padang, provides impact Which profitable (positive spillovers) like reduce burden government For provide field Work, help process cycle recycling several types of waste, becoming the best alternative for empowered groups buy low, as well as being barn reception zakat. This research aims to determine what factors influence MSME owners to give zakat and their preferences when distributing zakat. The sample used was 150 respondents who were MSME owners in Padang City using descriptive analysis and long-term and multi-long-term regression. From the research results, it was found that MSME owners’ desire to give zakat is largely determined by knowledge about zakat, level of confidence, level of commitment to worship, while for the distribution of zakat itself, MSME owners are more dominant in giving through the Agency. Amil Zakat / Zakat Amil Institute (BAZ/LAZ).